Complicated and uncomplicated acute appendicitis in pregnancy: a single center experience - Hasırcı, İsmail; Ulutaş, Mehmet Eşref (The European Research Journal, 2023)
Objectives: Acute appendicitis is the most common non-obstetric pathology requiring emergency surgery on pregnant women. The aim of the study is to show the effect of uncomplicated and complicated acute appendicitis on pregnancy. Methods: This study was conducted retrospectively at the Department of General Surgery of Konya City Hospital. Pregnant patients who underwent surgery for acute appendicitis from January 1, 2020, through December 31, 2021, were included in the study. The cases were divided into two groups as complicated and uncomplicated appendicitis and compared. The demographic, clinical, and laboratory findings of the patients were obtained by screening the patient files. The cases were divided into two groups as complicated and uncomplicated appendicitis and compared. Results: The study included 46 pregnant patients with a mean age of 25.9 years. The mean gestational age of the patients at the time of surgery was 16.5 weeks. Of the patients, 47.8% were in the first trimester. Open appendectomy was performed in 35 (76.1%) patients, and laparoscopic appendectomy in eight (17.4%). Seven (15.2%) appendicitis cases were complicated. A negative appendectomy was performed in two (4.3%) patients. Preterm labor was seen at a rate of 28.6% in the complicated appendicitis group and 5.1% in the uncomplicated appendicitis group (p = 0.04), and the mean operative times were 65.8 and 46.1 minutes, respectively (p < 0.001). Conclusions: Both postoperative complications due to surgery and obstetric complications increase in patients with complicated appendicitis; therefore, it is particularly important to closely follow up these cases.